Entrepreneurship education in art and design universities: A review of pedagogical approaches and their effectiveness - Jie, Song; Min, Wang (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the current state, effectiveness, and challenges of entrepreneurship education in art and design universities globally. Through a systematic literature review, the research analyzes traditional, innovative, and interdisciplinary mainstream teaching approaches and assesses their impact on students' entrepreneurial intentions and skills. The study identifies key challenges, including curriculum limitations, funding constraints, and misalignment between student interests and course requirements. Entrepreneurship education in art and design fields requires further integration of practical experience and theoretical knowledge to address the specific needs of creative industries. This research provides recommendations for universities, industries, and policymakers to optimize entrepreneurship education in creative sectors and proposes future research directions such as digital art entrepreneurship and cultural heritage entrepreneurship.